Sanctioned Violence in the New Testament. (July 2017) - Carter, Warren
After describing key interpretive categories of sanctioned and structural violence, the article identifies some forms of sanctioned structural violence evident in Matthew's Gospel. It concludes with a brief consideration of contemporary strategies for identifying and resisting scriptural inscribing and sanctioning of violence.